Problems of restoration of easel graphics of the late 18th to early 20th centuries depicting castles of Galicia - Oleshchuk, Maksym (Art and Design, 2025)
The blossoming of typography in galicia during the late 18th and early 20th centuries helped popularise engravings depicting castle architecture. A significant portion of these structures are now either lost or ruined, highlighting the urgent need for their professional restoration as a vital component of preserving ukraine's cultural heritage. The aim of this article was to investigate the challenges and specific characteristics of restoring and conserving late 18th to early 20th-century engravings featuring galician castles, as well as to analyse methods for reconstructing lost parts of these architectural objects. The methodology included analysing historical engravings of galician castles, researching the techniques and materials used in their creation, and reviewing modern restoration and conservation methods. The article provided an in-depth analysis of the engraving restoration process, particularly the reconstruction of lost sections of architectural images. It identified the primary issues restorers face, such as paper degradation, ink fading, and mechanical damage. Considering the article's objective – focusing on the peculiarities of restoring castle engravings from the late 18th to early 20th century – the conducted research revealed the main problems in preserving and restoring these artworks. The article explored approaches to reconstructing lost fragments of images, with a particular emphasis on working with the architectural details of castles. Special attention was paid to the specific nature of restoring and conserving engravings from the period under investigation, taking into account their creation techniques and the materials used. The importance of this research lies in its ability to offer practical recommendations for restorers, art historians, and historians working with similar graphic materials. The findings will contribute to the development of scientifically sound methodologies for preserving valuable historical images of galician castle architecture for future generations. Furthermore, the article's content will be beneficial in museum work, archival practice, and in preparing scholarly publications on art and architectural history.